Do corporate sustainability practices enhance organizational economic performance?. Issue 2 (15th June 2015) - Maletic, Matjaž; Maletic, Damjan; Dahlgaard, Jens; Dahlgaard-Park, Su Mi; Gomišcek, Boštjan
Abstract : Purpose: – The purpose of this study is to clarify the relation between sustainability practices and financial and market performance, and also, the role of non-financial performance outputs in this relation. Corporate sustainability is a growing area of importance for organizational development. Managing sustainability practices successfully is an imperative in achieving competitive advantage. Design/methodology/approach: – Using empirical data based on a large-scale survey among organizations in five countries (i.e. Germany, Poland, Serbia, Slovenia and Spain), this paper utilized mediation analysis to estimate and test the mediated effects in a multiple mediator model. As such, the sizes of indirect effects of sustainability practices on financial and market performance through potential mediators were estimated. Findings: – The results showed that innovation performance exerts a mediation effect in the relation between sustainability practices and financial and market performance. The main conclusion is that a greater engagement in sustainability practices leads to an increased innovation performance, which in turn leads to financial and market performance. Originality/value: – This paper is one of the first attempts to empirically validate sustainability exploitation and sustainability exploration practices. Besides, the analysis of the direct and indirect effects of sustainability exploration and sustainability exploitation practices on financial and market performance has not been yet addressed to a great extent.